Strength of Problematic Soil Stabilised with Gypsum and Palm Oil Fuel Ash - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Muhammad Khairul Faiz, Jamal (Penerbit UMP, 2024)
Soil stabilisation technique becomes one of the techniques for solutions to problematic methods of soil improvement. This method is one of the techniques that are categorised as a new alternative to soil engineering problems as well as taking into account the impact of wasted materials and waste in the oil palm industry which is the industry that drives the country to the second largest producer in Asia. Palm oil fuel ash is used as a substitute for cement that reacts chemically to increase shear strength and problematic soil bearing ability. Kaolin is used as a problematic soil sample to study. To strengthen the mixture between kaolin and palm oil fuel ash, gypsum is also added as a catalyst during chemical reactions between mixed materials to be more effective. To determine the level of improvement in soil shear strength, laboratory tests, namely the Unconfined Compression Test (UCT) were implemented. Kaolin provides as control sample in addition to gypsum at the consumption level of 6% continuously mixed together with 4% of the palm oil fuel ash that are determined at the percentage level of 4%, 8% and 12 % separately that later been divided into four (4) different samples according to the respective mixture that has been determined for the research study. The highest improvement that was recorded is reaching to 192.40% increases on the 30th day of curing from the mixed samples which is the mixtures of Kaolin with 6% of gypsum and 12% palm oil fuel ash. This elucidates that both gypsum and POFA are the potential soil stabilisers.